1988
DOI: 10.1002/jts.2490010210
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and physical abuse in the schools: A paradigm for understanding post‐traumatic stress disorder in children and youth

Abstract: The literature on Post‐Traumatic Stress Disorder (PTSD) in children is rather sparse. Most accounts describe only the aftereffects of horrendous traumas. Yet there is evidence that children are also vulnerable to a wider range of stressor than adults. Since the nosology for PTSD is based upon adult psychopathology, there is a need to examine the syndrome in light of current knowledge about development, psychopathology, and ecological factors in children's lives. The purpose of this paper is to present evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Recent research suggests that ETV during childhood and adolescence perpetuates violence (Dodge, Bates, & Petit, 1990 ;DuRant, Cadenhead, Pendergast, Slavens, & Linder, 1994 ;Farrington, 1991 ;Gelles & Conte, 1990 ;Patterson, 1986 ;Patterson, Debaryshe, & Ramsey, 1989 ;Straus, 1991 ;Widom, 1989) and contributes to the development of emotional problems (Bell & Jenkins, 1990 ;Boney-McCoy & Finkelhor, 1995 ;DuRant, Getts, Cadenhead, Emans, & Woods, 1995 ;Fantuzzo et al, 1991 ;Freeman, Mokros, & Poznanski, 1993 ;Hyman, Zelikoff, & Clarke, 1988 ;Lyons, 1987 ;Martinez, Richters, & Benoit, 1993 ;Osofsky et al, 1993 ;Richters, 1993). One of the more frequently discussed effects of ETV is the development of post-traumatic stress disorder (PTSD ; Fitzpatrick & Boldizar, 1993 ;Pynoos & Eth, 1984 ;Pynoos, Frederick, Nader, & Arroyo, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that ETV during childhood and adolescence perpetuates violence (Dodge, Bates, & Petit, 1990 ;DuRant, Cadenhead, Pendergast, Slavens, & Linder, 1994 ;Farrington, 1991 ;Gelles & Conte, 1990 ;Patterson, 1986 ;Patterson, Debaryshe, & Ramsey, 1989 ;Straus, 1991 ;Widom, 1989) and contributes to the development of emotional problems (Bell & Jenkins, 1990 ;Boney-McCoy & Finkelhor, 1995 ;DuRant, Getts, Cadenhead, Emans, & Woods, 1995 ;Fantuzzo et al, 1991 ;Freeman, Mokros, & Poznanski, 1993 ;Hyman, Zelikoff, & Clarke, 1988 ;Lyons, 1987 ;Martinez, Richters, & Benoit, 1993 ;Osofsky et al, 1993 ;Richters, 1993). One of the more frequently discussed effects of ETV is the development of post-traumatic stress disorder (PTSD ; Fitzpatrick & Boldizar, 1993 ;Pynoos & Eth, 1984 ;Pynoos, Frederick, Nader, & Arroyo, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated more traumatic reactions in younger children (e.g. Hyman, Zelikoff & Clarke, 1988;Rigamer, 1986), while others have failed to find age effects (e.g. Pynoos et al, 1987;Terr, 1979).…”
mentioning
confidence: 99%
“…The second section of the interview guide for parents and teachers, 'Children's Behaviour Following Trauma', included questions relating to post-trauma behaviour as described in the DSM-IV (APA, 1994), the Impact of Event Scale (Horowitz et al, 1979) and in previous studies in this area (Pynoos et al, 1987;Hyman et al, 1988;Yule & Williams, 1990). The final section, 'School Role Performance', included questions regarding the occupational performance of the role of a school student.…”
Section: Interview Guidesmentioning
confidence: 99%
“…Studies of children's responses to traumatic events have focused on the diagnosis of PTSD and a description of PTSD symptomatology through the use of scales and checklists. Hyman et al (1988) developed a school trauma survey to describe the pattern of PTSD symptoms in children. The authors identified a subset of symptoms related to abuse in schools and proposed that these symptoms are common to the problems of severe stressors in the lives of children.…”
Section: Introductionmentioning
confidence: 99%